Regulation of house arrest as a precautionary measure in Ecuadorian criminal proceedings - Toaquiza Díaz, Jhony Marcelo (USFQ Law Review, 2025)
In the Ecuadorian criminal justice system, precautionary measures are essential to ensure the effectiveness of the investigation and prosecution, as well as to protect victims and society until the final verdict is issued. The Comprehensive Organic Criminal Code includes several measures of a real and personal nature. Within the second group —which directly affects the accused person— it classifies house arrest as a measure restricting liberty, but in the individual's home, preventing entry into a detention center.With these considerations, in countries such as Spain, Colombia, and Peru, house arrest is viewed as a mitigated form of pretrial detention, regardless of the place of execution. Their highest courts have emphasized that individuals under this measure are legally deprived of liberty; therefore, they establish clear requirements for admissibility to avoid legal loopholes, unequal judicial decisions, and the potential impact on legal certainty. However, unlike these countries, such prerequisites for issuing sentences do not exist in Ecuador. The lack of criteria regarding the institution of house arrest in the country is segregationist in the face of the institutional development of pretrial detention, posing a risk to due process. In this context, this research seeks to analyze these aspects and highlight the need to implement admissibility requirements for the application of house arrest in Ecuador, ensuring its proper use and preventing arbitrary practices.
Keywords: Criminal proceedings; precautionary measures; house arrest; deprivation of liberty; requirements; legal reform